2016
DOI: 10.1007/s11010-016-2821-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial over-expression of soluble epoxide hydrolase (Tie2-sEH) enhances adenosine A1 receptor-dependent contraction in mouse mesenteric arteries: role of ATP-sensitive K+ channels

Abstract: Soluble epoxide hydrolase (sEH) converts epoxyeicosatrienoic acids that are endothelium-derived hyperpolarizing factors into less active dihydroxyeicosatrienoic acids. Previously, we reported a decrease in adenosine A1 receptor (A1AR) protein levels in sEH knockout (sEH−/−) and an increase in sEH and A1AR protein levels in A2AAR−/− mice. Additionally, KATP channels are involved in adenosine receptor (AR)-dependent vascular relaxation. Thus, we hypothesize that a potential relationship may exist among sEH overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 39 publications
(74 reference statements)
2
36
0
Order By: Relevance
“…This in turn could lead to higher levels of 20-HETE. This possibility is supported by the finding that CYP4A’s expression was increased in the mesenteric arteries of Tie2-sEH Tr mice [12]. The levels of 20-HETE were too low to be detected in heart perfusates from WT or Tie2-sEH Tr mice.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This in turn could lead to higher levels of 20-HETE. This possibility is supported by the finding that CYP4A’s expression was increased in the mesenteric arteries of Tie2-sEH Tr mice [12]. The levels of 20-HETE were too low to be detected in heart perfusates from WT or Tie2-sEH Tr mice.…”
Section: Discussionmentioning
confidence: 92%
“…CYP4A is an ω-hyroxylase involved in metabolizing AA to the potent vasoconstrictor 20-HETE [16]. Yadav et al has recently reported that CYP4A level was increased in the mesenteric arteries of Tie2-sEH Tr mice [12]. These data suggest that while the decrease in mid-chain HETEs observed in the heart perfusates of Tie2-sEH Tr mice should have enhanced CRH, the reported increased expression of CYP4A in the same mice may have overridden the effect of decreased mid-chain HETEs and caused a net effect of decreased CRH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations